Oro masių trajektorijų grupavimo metodo taikymas ozono koncentracijų analizei - Byčenkienė, Svetlana; Girgždienė, Raselė (2005)
In this paper the trajectory clustering method for ozone investigation was applied. The joined air masses trajectories and chemistry data were subsequently filtered and analyzed according to indicated requirements. South and north "filters" areas were specified in latitude/longitude coordinates, which were passed by the trajectories. Furthermore, a height filter was specified, where trajectories were below an indicated height over the 1997-1999 period. Using box-clustering algorithm the "box" located over the Atlantic region was defined. Both groups of air masses trajectories passed this "box" during the first 5 days before reaching the continent. In summer the episodes with higher ozone concentration were related with air masses from the south (France, Germany, Belgium, Austria, Poland). On the contrary, ozone lower mean concentrations were associated with air masses from the north region (Iceland, Norway, Sweden, Finland).